PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SMP MUHAMMADIYAH 07 MEDAN PERJUANGAN TAHUN PELAJARAN 2018/2019 - Lubis, Maulana Arafat; Azizan, Nashran (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
The objectives of the study were, to find out the result of student in learning Math before and after using problem based learning model, to find out whether problem based learning model able to improve students’ ability in learning Math. The material topic was Addition and Reduction of integer operations. The subject of the study were 33 students at the seventh grade of SMP Muhammadiyah 07 Medan Perjuangan in academic year 2018/2019. The object of the study was problem based learning model in improving students’ ability in learning math with th topic Addition and Reduction of integer operations. The data were collected by using test, observation, documentation and interview. The data were analyzed in several steps, they were: data reduction, data display, and verifiying/conclusion. The result of students’ ability in learning math before using problem based learning model was low. It was represented by percentage of students’minimum mastery criteria only 15,15% with average 52,27. After using problem based learning model, students’ ability was improved. The percentage of students’ minimum mastery criteria was 60,60% and 75 at the end of cycle I and 90,90% and 87.57 at the end of cycle II. As a result, the using of problem based learning model in learning math with topic Addition and Reduction of integer operations was able to improve the ability og the seventh grade students of SMP Muhammadiyah 07 Medan Perjuangan in academic year 2018/2019.